2014
DOI: 10.3892/ol.2014.2326
|View full text |Cite
|
Sign up to set email alerts
|

Hyperleukocytosis: A report of five cases and review of the literature

Abstract: Hyperleukocytosis (white blood cell count, >100×109/l), an uncommon presentation of leukemia, is associated with an increased risk of early mortality. It may present with a variety of symptoms secondary to leukostasis, a syndrome caused by the sludging of circulating leukemic blasts in the microvasculature. Adequate measures for managing this medical emergency include hydration, cytoreduction, prevention of tumor lysis and, rarely, leukapheresis in cases complicated by leukostasis and hyperviscosity syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…It has been reported that minor surgeries, such as dental extraction, can be performed when the platelet count is > 40,000/mm 3 ; the normal platelet count ranges from 150,000 to 400,000/mm 3 [4,5,7,14]. When dental extractions are anticipated, Hb concentrations of ≧ 5.5-8 g/dL are required for effective hemostasis and reduced risk of bacterial infection [5,6,11,21].…”
Section: Preoperative Anesthetic Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that minor surgeries, such as dental extraction, can be performed when the platelet count is > 40,000/mm 3 ; the normal platelet count ranges from 150,000 to 400,000/mm 3 [4,5,7,14]. When dental extractions are anticipated, Hb concentrations of ≧ 5.5-8 g/dL are required for effective hemostasis and reduced risk of bacterial infection [5,6,11,21].…”
Section: Preoperative Anesthetic Assessmentmentioning
confidence: 99%
“…Pediatric cancer is a common cause of disease-related fatality in children [1][2][3]. The common pediatric malignancies are leukemia (30%) and central nervous system (CNS) tumors (22%) [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, certain patients with acute leukemia present with clinical signs of hyperleukocytosis [13].…”
Section: % 16%mentioning
confidence: 99%